PWE-267 Has the publication of surgeon specific data adversely affected older patients?. (22nd June 2015) - Ghanbari, A; Evans, J; Chokkarapu, P; Kang, P; Khalil, K; Hunter, D
Abstract : Introduction: The Association of Coloproctology first published surgeon specific outcome data in September 2013. There has been some concern this may lead to surgeons refusing to operate on higher risk patients. Furthermore, Published by the Royal College of Surgeons of England, "Access Ages 2" suggests that there is a marked decline in rates of elective surgery in over 65s. It described a 9 fold difference in the rate of colorectal cancer excision for over 75s depending on where the patient lives. We hypothesised that concern over poor outcomes may lead to a reduction in the age of patients offered elective colorectal cancer excision. Method: Data was prospectively collected on all patients undergoing elective colorectal cancer resections in our unit. We compared the patient selection for one year before and after publication of surgeon specific data. Results: In the 12 months prior to publication of surgeon specific data, our Unit (4 Consultant Colorectal Surgeons) operated on 114 patients with a median age of 71 (IQR 63–77.5), compared to 84 patients with a median age of 72.5 (65–77) for the subsequent 12 months (p = 0.351, Mann-Whitney). There were more patients in the 75–85 age range than in the 65–75 range. The comorbidities identified in both groups were comparable. Conclusion: There was no difference in the age group of patients offered elective surgery following the publication of surgeon specific outcome data. Fears that the publication may lead to older patients being denied surgery were unfounded. Disclosure of interest: None Declared. Reference: http://www.rcseng.ac.uk/news/docs/access-all-ages-2